Fontan Conversion: Literature Review and Lessons Learned Over 20 Years. (March 2016) - Mavroudis, Constantine; Deal, Barbara J.
Early survival after the Fontan operation has improved significantly leading to a lifetime of Fontan circulation for patients. There is a natural progression of pulmonary artery pressure during the human lifetime that is easily tolerated in two-ventricle physiology but is deleterious for single-ventricle physiology. Obstructions in the venous to pulmonary artery pathway and pulmonary venous return or ventricular outflow, atrioventricular valve dysfunction (regurgitation), pulmonary arteriovenous malformations, venous thrombosis, and the development of atrial arrhythmias can lead to reduced functional status. These complications have been demonstrated in older patients with largely atriopulmonary connections owing to time accrual and unfavorable flow characteristics. Various surgical and catheter interventions aimed at reducing morbidity and mortality have been attempted to treat these identifiable abnormalities. The purpose of this article is to review the extant literature on Fontan Conversion and to assess the lessons learned over 20 years.